Under his wings : how faith on the front lines has protected American troops - Compagno, Emily, 1979- (Fox News books, 2024)
"In this celebration of faith and freedom, Fox News Co-Host Emily Compagno shares first person accounts that show the profound role belief in God has played in the lives of U.S. military servicemembersas they served in combat from World War I to today--commemorating the courage, camaraderie, spirit, and sacrifice of America's heroes."--Provided by publisher.